Volunteer Interpersonal Communication Fosters Motivation/Self Development in Complex-Background Foster Children at S3 Lintau - Melda Riani; Ernita Arif; Asmawi Asmawi (Journal of Social Research, 2025)
This research examines interpersonal communication based on intuition, bypassing institutional formalities, yet effectively fostering motivation and self-development in children from complex social backgrounds at the S3 Lintau Foster Home. Children with challenging backgrounds need supportive care and effective communication from family figures to build self-confidence, motivation, and growth. This study reveals that volunteers, through adaptive communication and intuition, successfully fulfill this needs. The research aims to analyze how volunteers' interpersonal communication processes contribute to motivating and developing foster children at the S3 Lintau Orphanage. Utilizing a qualitative case study approach, researchers apply Joseph DeVito’s interpersonal communication concepts alongside the Theory of Coordinated Management of Meaning (CMM) to deeply investigate communication flows. Findings highlight the significance of verbal and nonverbal communication that is personalized for each foster child. The process begins by building closeness, followed by supportive and empathetic message delivery, internalization of rules and values, encouragement of competent behavior, and ultimately fostering motivation and self-development. This progression relies heavily on reconstructing and coordinating meanings to establish shared understanding of the values, rules, and motivations imparted. The study demonstrates how volunteers, without formal authority, use intuitive and adaptive interpersonal communication to meet the emotional and developmental needs of foster children in a complex social context, effectively promoting their growth and motivation.